A Progress Report on Metal–Sulfur Batteries. (16th August 2020) - Yu, Xingwen; Manthiram, Arumugam
Abstract: Nonaqueous conversion‐reaction sulfur chemistry has been attracting increasing attention over the past decade for the development of next‐generation lithium‐based batteries. Li–S batteries are currently approaching a nexus stage from lab‐scale experiments to possible pragmatic applications. Inspired by the success of Li–S chemistry, other metal–sulfur batteries with a variety of metallic anodes, such as sodium, potassium, magnesium, calcium, and aluminum, have also started to attract attention. In comparison to lithium, Na, Mg, Al, K, and Ca are naturally more abundant and affordable. The Na‐S, Mg‐S, Al‐S, K‐S, and Ca‐S battery systems provide a great potential for improving the volumetric energy density of sulfur‐based batteries. The multivalent metal‐sulfur systems, Mg‐S, Al‐S, and Ca‐S, offer better safety features as well. However, the research and development on Na‐S, Mg‐S, Al‐S, K‐S, and Ca‐S batteries is far behind the Li–S system due to many critical challenges. In this progress report, the fundamental principles of various metal–sulfur chemistries are first presented and compared. Then, the historical progress, recent advances, and key challenges of the Li–S, Na‐S, Mg‐S, Al‐S, K‐S, and Ca‐S systems are summarized and discussed. Finally, future efforts and directions for both the fundamental and practical research are prospected. Abstract : Research progress and critical challenges of room‐temperature metal–sulfur batteries (Li–S, Na‐S, K‐S, Mg‐S, Ca‐S, and Al‐S) are comprehensively summarized and rationally analyzed in terms of their electrochemical reaction mechanisms, technical advances, and materials development. Future research directions are prospected toward making the metal–sulfur energy‐storage systems a viable technology with acceptable performance.